FORMATION OF THE CONCEPT OF DEATH AMONG HEALTHY AND CANCER SICK CHILDREN OF YOUNGER SCHOOL AGE - Hakobyan , N.R.; Khachatryan, A.G. (Modern Psychology, 2021)
The purpose of the study is to present the psychological characteristics of the concept of death among children of younger school age, consideration from the point of view of determining the relationship of the children to death, identifying differences between healthy and cancer sick children regarding death ideas. This formulation of the scientific problem allows us to investigate the installation of a mature idea of death, prevention of anxiety, and the motivation of a positive attitude to life. The research is particularly relevant today when the process of psychological acceleration of the child development occurs. An integrated approach to studying the formation of the death concept among children is not represented only among healthy children, but among cancer sick children. The problem of the formation of the death concept acquires new values in the conditions of serious illness of the child, when the child must face the fear of death. The significance of the results of the study is identified by the development of positive life attitudes. The practical significance of the work is also shown in the prospects for the further implementation of the data obtained and the prevention of anxiety in the process of formation the concept of death.